Penilaian Tingkat Kesehatan Bank: Pendekatan CAMEL Dan RGEC - Erika Amelia; Astiti Chandra Aprilianti (SEKOLAH TINGGI EKONOMI ISLAM SEBI, 2018)
This study aims to determine the risk based bank rating at PT. Bank Maybank SyariahIndonesia if measured using CAMEL (Capital, Asset, Management, Earning,Liquidity) method and RGEC (Risk Profile, Good Corporate Governance, Earning,Capital) in 2011-2016 and also aims to know differences in ratios used in CAMELSand RGEC methods. The research method used in this research is literature researchor study desk study. The data used in this research is secondary data using financialstatements of Bank Maybank Syariah Indonesia Period 2011-2016. The results showthat the bank can be said to be adequately sound because almost all the ratios usedmeet the specified requirements and there are still some ratios that have not met therequirements, but in both methods have different results. In the year 2011-2014 therisk based bank rating of Maybank Syariah Bank is calculated using CAMEL methodof bank is in the sound level. In 2015 -2016, the calculation of bank soundness showsthat bank condition is in an sound level. In Maybank Syariah Bank the state of thebank is in the sound level is in 2011-2013 if calculated using the RGEC method. Inthe year 2014-2016 the condition of the bank shows a adequately sound level.